The evaluation of the video assistant referee from referees` and spectators` perspectives in soccer - A case study of the German Bundesliga - Schwab, S.; Steverding, P.; Rein, R. (Soccer & Society, 2023)
Fairness is one of the key requirements for sport. Thus, the refereeing must be impartial. Therefore, to ensure that a referee can make verifiable correct decisions increasingly technical aids are used during live play. In soccer, next to goal-line technologies (GLT), the introduction of a Video Assistant Referee (VAR) was a major step to increase fairness in decision-making. Accordingly, the present study aimed to further investigate how the VAR in soccer is accepted and whether there is a difference between soccer referees` and fans` perceptions regarding the VAR. Therefore, self-identified soccer fans and/or former or active referees were contacted through various outlets leading to 1.442 completed questionnaires. The results indicated that soccer referees evaluate the VAR more positively compared to soccer fans. This supports previous research regarding the VAR but highlights the need for soccer associations to further educate spectators about the merits of the VAR.